Factors affecting awareness of preparedness after moderate earthquakes: An analysis of the Pohang earthquake in Korea. Issue 3 (25th December 2019) - Moon, Ji-Won; Hwang, Ha; Chung, Ji-Bum
Abstract : Purpose: The purpose of this paper is to examine how experiencing moderate earthquakes influences risk perception and preparedness. Design/methodology/approach: An online survey was conducted on a nationally representative sample of Korean adults after the moderate earthquake in Pohang in 2017. Statistical analyses were conducted to identify the determinants of willingness to pay (WTP) for seismic retrofitting and earthquake insurance. Findings: The results show that risk perception, housing ownership, earthquake experience and income level significantly influenced WTP for seismic retrofitting and earthquake insurance. The results also indicate that a greater number of damage-free earthquake experiences reduced the WTP that could be explained by normalcy bias. Finally, people who believed that the Pohang earthquake might be an example of induced seismicity (i.e. triggered by the geothermal power plant) tended to have a lower WTP for seismic retrofitting. Originality/value: This study offers valuable findings on public attitudes about enhancing earthquake preparedness policies in moderate earthquake zones, regions that few studies have examined despite their high vulnerability due to a lack of preparedness.